Criminal Acts Of Gambling And Its Countermeasures In Pohuwato Regency - Ayu Pian Djailolo (Estudiante Law Journal, 2019)
Abstract: This research aims to find out how the village government's efforts in winning gambling crimes in Kabupaten Pohuwato. The type of research used in this research is a type of empirical legal research. Efforts made by the village government against the countermeasures of gambling crimes in central Buntulia village in the form of socialization and socialization by providing understanding to the perpetrators are carried out by the village government in collaboration with police officers about the impact of playing gambling both legally and socially and The economy is both done in forum activities or directly in gambling locations. Furthermore, agreeing on the perpetrator who was caught while practicing gambling than by the police and the village government will give a warning and agree the perpetrators and the police officers in the form of an affidavit that the concerned will not repeat his actions. Then against the perpetrator who has made an agreement with the village government but was eventually caught playing gambling, it will then be handed over to the police for processing by the provisions of applicable law. Keywords:  Countermeasures, Criminal Acts, Gambling